2014
DOI: 10.1530/joe-13-0444
|View full text |Cite
|
Sign up to set email alerts
|

Combined galanin with insulin improves insulin sensitivity of diabetic rat muscles

Abstract: Although administration of galanin or insulin alone may enhance insulin sensitivity and glucose transporter 4 (GLUT4) trafficking, their cooperative effect on insulin sensitivity is still unclear. In the present study, we evaluated the cooperative effect of both reagents compared with solitary treatment with galanin or insulin in type 2 diabetic rats. Galanin and/or insulin were injected singly or together into type 2 diabetic rats once a day for 15 days. The results indicated that coadministration of both rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
2
20
0
3
Order By: Relevance
“…Our previous studies found that treatment with a galanin antagonist, M35, decreased GLUT4 translocation and glucose uptake in adipocytes, i.e., endogenous galanin can elevate GLUT4 translocation and glucose uptake in diabetic rats [2]. Furthermore, Bu et al found that galanin may benefit insulin-induced GLUT4 translocation and subsequent glucose uptake [5]. In line with these studies, the present results revealed that co-administration of galanin and insulin compared to treatment with either hormone individually significantly increased [ 3 H]2-DG influx and GLUT4 and VAMP2 translocation, but reduced blood glucose levels, further manifesting that injection of galanin can facilitate insulin-stimulating glucose uptake in the adipocytes of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies found that treatment with a galanin antagonist, M35, decreased GLUT4 translocation and glucose uptake in adipocytes, i.e., endogenous galanin can elevate GLUT4 translocation and glucose uptake in diabetic rats [2]. Furthermore, Bu et al found that galanin may benefit insulin-induced GLUT4 translocation and subsequent glucose uptake [5]. In line with these studies, the present results revealed that co-administration of galanin and insulin compared to treatment with either hormone individually significantly increased [ 3 H]2-DG influx and GLUT4 and VAMP2 translocation, but reduced blood glucose levels, further manifesting that injection of galanin can facilitate insulin-stimulating glucose uptake in the adipocytes of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The six treatment groups were injected with galanin (1 nmol·kg -1 , i.v. reference to Bu’s experiment [5]), insulin glargine (2 U·kg -1 , s.c.) and MK-2206 (300 μg·kg -1 , i.v. reference to Li’s experiment [10]), either individually or in combination.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations